Findings from the DUMA program: methamphetamine drug market trends - Sarah Coghlan
Introduction Methamphetamine is a drug of national concern, with the Australian Crime Commission assessing it to be the illicit drug posing the greatest risk to the Australian community. The Australian Institute of Health and Welfare’s (AIHW) 2013 National Drug Strategy Household Survey (NDSHS) reported that approximately 400,000 Australians had used meth/amphetamines in the previous 12 months. The NDSHS reported a stable rate of meth/amphetamine use in the general community from 2010 to 2013 of 2.1 percent. However, there was a shift in the type of meth/amphetamine used, from powder to purer forms like ice or crystal methamphetamine. Specifically, powder meth/amphetamine use among recent users decreased from 51 percent to 29 percent, while ice use more than doubled from 22 percent to 50 percent. In line with this, the frequency of methamphetamine use among injecting drug users in Melbourne remained consistent from 2008 to 2014, but users reported transitioning from powder to crystal forms of methamphetamine. Frequency of use of methamphetamine has also changed across the 2010 to 2013 period. In 2013, 15.5 percent of recent meth/amphetamine users reported daily or weekly use, compared with 9.3 percent in the 2010 survey. When examining use by form, approximately a quarter of users who mainly used ice reported using it at least weekly, compared with 2.2 percent of powder users who reported weekly use. Scott et al.’s study of injecting drug users in Melbourne found that those already using methamphetamine were starting to purchase the drug more frequently in 2013 compared with 2011